Developmental life history is associated with variation in rates of climatic niche evolution in a salamander adaptive radiation - Shepard, Donald; Weaver, Samuel; Kozak, Kenneth (Dryad, 2020)
Rates of climatic niche evolution vary widely across the tree of life and
are strongly associated with rates of diversification and the accumulation
of species diversity among clades. However, why the climatic niche evolves
more rapidly in some lineages than others remains unclear. Variation in
life history traits often plays a key role in determining the
environmental conditions under which species can survive, and therefore,
could impact the rate at which lineages can expand in available climatic
niche space. Here, we explore the relationships among life-history
variation, climatic niche breadth, and rates of climatic niche evolution.
We reconstruct a new phylogeny for the genus Desmognathus, an adaptive
radiation of salamanders distributed across eastern North America, based
on nuclear and mitochondrial genes. Using this phylogeny, we estimate
rates of climatic niche evolution for species with long, short, and no
aquatic larval stage. Rates of climatic niche evolution are unrelated to
the mean climatic niche breadth of species with different life histories.
Instead, we find that the evolution of a short larval period promotes
greater exploration of climatic space, leading to increased rates of
climatic niche evolution across species having this trait. We propose that
morphological and physiological differences associated with variation in
larval stage length underlie the heterogeneous ability of lineages to
explore climatic niche space. Rapid rates of climatic niche evolution
among lineages with short larval periods were an important dimension of
the clade’s adaptive radiation and likely contributed to the rapid rate of
lineage accumulation following the evolution of an aquatic life history in
this clade. Our results show how variation in a key life-history trait can
constrain or promote divergence of the climatic niche, leading to
variation in rates of climatic niche evolution among lineages.
The following files are included: Desmog_24taxa11loci_concatenated.nex
contains the aligned, concatenated DNA sequences for all 11 loci for
single exemplars of each species. Partitions are included in a mrbayes
block below the DNA sequences. Desmog_24taxa11loci_chronogram.nex is the
BEAST chronogram from the concatenated analysis.
Desmog_62taxa11loci_alignments.zip contains the phased DNA sequence
alignment (nexus format) of each of the 11 loci used in the species tree
analysis. Also included is starBEAST_speciestraits.txt which assigns each
of the 62 individuals to one of 24 species.
Desmog_62taxa11loci_speciestree.nex is the species tree from the *BEAST
species tree analysis of 11 loci for 62 individuals of 24 species.
Desmog_coords_bioclim_data.xlsx contains tab 1: latitude and longitude for
localities of each species and the bioclim variables for those localities,
tab 2: snout-vent length (SVL in mm), larval period, and microhabitat of
each species. Supplemental_Tables.docx contains tables S1: information on
DNA loci and primers, S2: nucleotide substitution models used for each
locus in analyses, and S3: specimen/sample information.
Keywords: Desmognathus; niche evolution; climatic niche; developmental mode; climatic niche